ANALISIS GANGGUAN PERKEMBANGAN BAHASA ANAK (SPEECH DELAY) - Sauma Fitri; Najwa Muthmainnah; Shabrina Saleem; Hijriati (STKIP Subang, 2026)
Speech delay, or delayed language development, is a developmental disorder increasingly found in early childhood. In recent years, the development of digital technology has changed the patterns of children's interactions with their social environment. Excessive use of gadgets, reduced verbal interaction between parents and children, and low language stimulation have become issues frequently associated with the rise in cases of speech delay. This phenomenon is gaining increasing attention because language skills are a crucial foundation for children's cognitive, social, emotional, and academic development. This study aims to analyze the factors causing speech delay in children and examine its relationship to the increasing use of digital media in everyday life. This study used a literature review method by examining various scientific articles, health reports, and international publications published in the past five years. The results indicate that speech delay is influenced by various factors, including biological, environmental, psychosocial, and digital technology. Excessive screen time has been shown to be associated with low frequency of verbal interaction between children and parents, which impacts vocabulary development and children's communication skills. Furthermore, delayed early detection and parents' lack of understanding of the stages of language development contribute to this condition. Therefore, collaborative efforts between families, healthcare professionals, educators, and the government are needed to raise awareness of the importance of early language stimulation. Early intervention, limiting device use, and improving the quality of parent-child interactions are key strategies in preventing and treating speech delay in children.